Entrevista com Fernanda Coelho Liberali - Liberali, Fernanda Coelho; Miller, Inés; Bezerra, Isabel C. R. Moraes (SOLETRAS, 2018)
Entrevista concedida às professoras Inés Kayon de Miller e Isabel Cristina Rangel Bezerra